Challenges of knowledge representation in contemporary archival science - Tognoli, Natália Bolfarini [UNESP]; Guimarães, José Augusto Chaves [UNESP] (My University, 2012)
Since its emergence as a discipline, in the nineteenth century (1889), the theory and practice of Archival Science have focused on the arrangement and description of archival materials as complementary and inseparable nuclear processes that aim to classify, to order, to describe and to give access to records. These processes have their specific goals sharing one in common: the representation of archival knowledge. In the late 1980 a paradigm shift was announced in Archival Science, especially after the appearance of the new forms of document production and information technologies. The discipline was then invited to rethink its theoretical and methodological bases founded in the nineteenth century so it could handle the contemporary archival knowledge production, organization and representation. In this sense, the present paper aims to discuss, under a theoretical perspective, the archival representation, more specifically the archival description facing these changes and proposals, in order to illustrate the challenges faced by Contemporary Archival Science in a new context of production, organization and representation of archival knowledge.